Synapse differentiation-induced gene 1 regulates stress-induced depression through interaction with the AMPA receptor GluA2 subunit of nucleus accumbens in male mice. (1st August 2022) - Jiang, Linhong; Zhang, Haoluo; He, Yuman; Liu, Haxiaoyu; Li, Shu; Chen, Rong; Han, Shuang; Zhou, Yuanyi; Zhang, Jiamei; Wan, Xuemei; Xu, Rui; Wang, Shaomin; et al.
Abstract: Alpha-amino-3-hydroxy-5-methyl-4-isoxazole propionic acid receptors (AMPARs) are key regulators during the process of synaptic plasticity in major depression disorder (MDD). Synapse differentiation-induced gene 1 (SynDIG1) functions as an atypical AMPAR auxiliary subunit and regulates synaptic AMPAR content; however, the role of SynDIG1 in MDD remains elusive. In this study, we found that the SynDIG1 expression was significantly increased in the neurons of the nucleus accumbens (NAc) of male mice after chronic social defeat stress (CSDS). CSDS enhanced SynDIG1-GluA2 binding and promoted the surface expression of AMPAR subunit GluA2 in the NAc. Knockdown of SynDIG1 decreased the surface expression of GluA2 and reversed the alteration of dendrite spines in the neurons, eventually alleviating the depressive-like behaviors of the stressed mice. Moreover, intra-NAc injection of IP12, a specific peptide to disrupt the interaction of SynDIG1 with GluA2, rescued depressive-like behaviors. Collectively, SynDIG1 regulates the surface expression of GluA2 and dendritic remodeling in the NAc of male mice under CSDS, thus mediating the depressive-like behaviors. Graphical abstract: Image 1 Highlights: Chronic stress increased SynDIG1 expression in the NAc. Chronic social defeat stress enhanced SynDIG1-GluA2 binding and promoted the surface expression of the AMPAR subunit GluA2. Blockade of SynDIG1 or disruption of SynDIG1-GluA2 interaction attenuated depressive-like behaviors by mediating structural dendritic spine.